Self-sampling in biomolecular tests beyond the prevention of cervical cancer - Campos Arze, Wilma Nancy; Campos Junior, José Eleutério; de Queiroz Varella, Renata (Brazilian Journal of Sexually Transmitted Diseases, 2024)
*